Position and Energy Resolution of a γ-Camera based on a Position Sensitive Photomultiplier Tube - Polychronopoulou, A.; Thanasas, D.; Giokaris, N.; Karabarbounis, A.; Maintas, D.; Papanicolas, C. N.; Stiliaris, E. (HNPS Advances in Nuclear Physics, 2020)
Studies of the spatial- and energy-resolution of a small field, high resolution γ-Camera system currently being developed in our laboratory are presented here. The system is based on a cylindrical Position Sensitive Photo-Multiplier Tube (HAMAMATSU R2486) with 32 crossed-wired anodes, arranged in two orthogonal groups. The anode outputs are connected to a resistive current divider network and after pre-amplification are guided to a local digitizing system. A PCI-Analog to Digital Converter card with a maximum sampling rate of 20 MHz and the rest of the Data Acquisition System is controlled by software running on the LabVIEW environment. Position and induced charge of the incident light pulses can be easily reconstructed through a variety of offline algorithms. In the first part of this study the intrinsic response of the PMT and especially its energy and position resolution is presented. The experimental procedure utilizes the controlled pulse light output of a LED guided through fiber glass directly to the PMT’s entrance. The accumulated charge distribution and charge spread as a function of the incident number of photons is studied. In the second part, the response of the integrated γ-Camera system after the application of typical scintillation crystals for 99Tc radioactive phantoms is measured and analyzed.